2006
DOI: 10.1007/s10029-006-0147-6
|View full text |Cite
|
Sign up to set email alerts
|

Hernia disease and collagen gene regulation: are there clues for intervention?

Abstract: Collagens belong to the most abundant proteins in the body. After tissue injury, a coordinated regulation of collagen gene expression guides the formation of a provisional matrix that subsequently evolves into a mature scar with tensile strength. In the following, knowledge regarding collagen gene regulation that may provide insight into how to specifically address the biological problem of soft tissue weakness and recurrent hernia disease is summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…This development has been previously described by Knight et al [26]. An increased amount of premature collagen type III is present in the early phase of wound healing which is later on being replaced by highly cross-linked and stable collagen type I [27]. A high collagen I/III ratio shows the maturing of the scar tissue, therefore demonstrating an adequate wound healing [15].…”
Section: Discussionmentioning
confidence: 65%
“…This development has been previously described by Knight et al [26]. An increased amount of premature collagen type III is present in the early phase of wound healing which is later on being replaced by highly cross-linked and stable collagen type I [27]. A high collagen I/III ratio shows the maturing of the scar tissue, therefore demonstrating an adequate wound healing [15].…”
Section: Discussionmentioning
confidence: 65%
“…A previously developed plasma coating strategy to optimize biocompatibility of meshes seems not to influence this early inflammatory reaction and inflammatory infiltrate formation but more so to influence mid- and long-term processes which lead to neovascularization, collagen fibre organisation. It has been shown that premature type III collagen is predominantly synthesized in early phases of wound healing and in the presence of inflammatory cells [15]. Collagen III is then replaced by highly cross-linked and stable collagen type I later after implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The study of hernias provides vast field of research on the cellular mechanisms, mutations and the ability to form collagen tissue, as well as on environmental factors and genetic alterations of this regulation, which are essential for proper postoperative healing. The progressive decrease of collagen with age, the changes of its ultrastructure, the further degradation and increased matrix proteases that accompany aging are also extensively studied, but several aspects not yet completely elucidated justify complementary research 13 15 26 . An important aspect of these studies is related to technologies involving the biophotonics, with laser employment (light amplification by stimulated emission of radiation), being an increasingly used option 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative adhesions represent a complex problem after the manipulation of the abdominal cavity 2 3 10 14 28 or situations that are accompanied by peritonitis 8 . Environmental factors such as smoking, factors that are inherent to the patient as obesity and genetics, as well as local complications of the incision, with wound infection, are important to the development of incisional hernias 13 15 26 . Published articles on the various options of synthetic prostheses used in the repair of such hernias 1 3 9 18 19 22 23 29 show that even the state-of-the-art materials, developed for direct contact with the abdominal cavity, despite decreasing, they can not completely prevent the formation of adhesions on these prostheses 4 22 23 25 , demonstrating that these materials need to be improved.…”
Section: Discussionmentioning
confidence: 99%